An event study of home and host country patent generation in Chinese MNEs undertaking strategic asset acquisitions in developed markets. Issue 5 (October 2015) - Anderson, John; Sutherland, Dylan; Severe, Sean
Highlights: We model the impact of Chinese strategic-asset related acquisitions on innovation. Such acquisitions do not impact innovation in acquired developed market firms. Domestic innovation in the Chinese parents, however, does improve. One explanation is Chinese MNEs deploy acquired strategic-assets domestically. Asset-seeking may therefore be strongly motivated by domestic market considerations. Abstract: We use event study methodologies to analyze trends in home and host country patent applications of Chinese MNEs that acquire strategic asset-rich developed market businesses. Our results show the domestic market patents of Chinese MNEs rise significantly in the wake of such acquisitions, while those of the acquired target do not significantly change. These results hold for different ownership classes. In light of current theoretical debates, we discuss the possible motivations for such acquisitions by Chinese MNEs and the reasons for the observed patenting performance in both domestic and target businesses. We argue acquisition of codified strategic assets (such as patents) for the purpose of imitation and exploitation in the domestic Chinese market context provides one plausible explanation for our results.